Qualidade de vida no trabalho de colaboradores de organizações localizadas na região dos Campos Gerais, Paraná, Brasil - Pilatti, Luís Eduardo (2021)
This study aims to evaluate the quality of work life for employees of organizations located in the Campos Gerais region, Paraná, Brazil. The sample consisted of 164 people employed in the administrative and technical areas identified through the author’s contact networks. The Total Quality of Work Life (TQWL-42) survey was used for data collection. To calculate the scores and perform descriptive statistics, we used the TQWL-42 syntax provided by the survey’s developers. On average, the QWL score was 0.65 (0.66 in the private sector; 0.58 in the public sector; 0.62 for technical roles; and 0.67 for administrative roles). The work life aspects most poorly evaluated by the sample population were extra benefits, financial resources, and health and social assistance services. The aspect with the best score was the ability to perform one’s work. We conclude that the surveyed groups present satisfactory levels of QWL, with a slightly higher perception of quality of work life among employees in the private sector and those in administrative roles. In general, employees have elevated levels of self-perception, work in satisfactory work environments, but are dissatisfied with their salary and benefits.